2020
DOI: 10.1021/acs.jcim.0c00063
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Further Thermostabilization of an Intrinsically Thermostable Membrane Protein Using Amino Acid Mutations with Its Original Function Being Retained

Abstract: We develop a new methodology best suited to the identification of thermostabilizing mutations for an intrinsically stable membrane protein. The recently discovered thermophilic rhodopsin, whose apparent midpoint temperature of thermal denaturation T m is measured to be ∼91.8 °C, is chosen as a paradigmatic target. In the methodology, we first regard the residues whose side chains are missing in the crystal structure of the wild type (WT) as the “residues with disordered side chains,” which make no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…It was previously shown that the mutation S162K is stabilizing, 14 but the present study suggests that the mutation F332K or F332R leads to higher stabilization. Of course, in general, many of the mutations for a membrane protein become stabilizing for different physical reasons and our statistical‐thermodynamics theory is capable of identifying such stabilizing mutations as previously demonstrated 10,15,20 …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It was previously shown that the mutation S162K is stabilizing, 14 but the present study suggests that the mutation F332K or F332R leads to higher stabilization. Of course, in general, many of the mutations for a membrane protein become stabilizing for different physical reasons and our statistical‐thermodynamics theory is capable of identifying such stabilizing mutations as previously demonstrated 10,15,20 …”
Section: Resultsmentioning
confidence: 75%
“…Of course, in general, many of the mutations for a membrane protein become stabilizing for different physical reasons and our statistical-thermodynamics theory is capable of identifying such stabilizing mutations as previously demonstrated. 10,15,20 F I G U R E 2 (a) Procedure of fluorescence screening followed. The library prepared was transformed by electroporation.…”
Section: Gene (Mutant) Library Constructed and Sorting Of Highly Stab...mentioning
confidence: 99%
“…In conclusion, the present thermo‐stabilization design in the extramembrane regions based on the free‐energy calculation and the subsequent evaluation by the MD simulation may be useful to improve the production of membrane proteins. The engineering in the intramembrane region 7,8 . would be a complementary design method.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a rational design of thermostable mutants is a desirable technology in the structural biology of membrane proteins. Recently, a computational method has been developed to identify possible thermo‐stabilizing mutations in the intramembrane region of a membrane protein 7,8 . However, there is no report to date for the rational thermo‐stabilization design in the extramembrane regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation